Vitamin D Deficiency: A common problem worldwide - Mahotra, Narayan Bahadur (Europasian Journal of Medical Sciences, 2020)
Sunlight exposure is the most important source of vitamin D for human beings. We can get vitamin D from other sources such as diet and dietary supplements as well. Human body synthesizes most of the vitamin D from exposure to direct Ultraviolet B (UVB) sunlight. Regular, short periods of UVB exposure during the summer months are enough to get required vitamin D for most people. Sunscreen might block the vitamin D synthesis process in skin. Solar ultraviolet B radiation (wavelength, 290 to 315 nm) penetrates the skin and converts7-dehydrocholesterol to provitamin D3, which is rapidly converted to vitamin D3. Excessive exposure to sunlight does not cause vitamin D3 intoxication but excess oral intake can cause intoxication. Therefore, we should be careful while taking dietary supplements of vitamin D. Regardless of the good sunlight exposure, surprisingly, the blood level of vitamin D is found to be low in people of South Asian countries including Nepal. No practice of sun bath and all the time body coverage with clothes could be the possible reason of low vitamin D level in this region of the world. Another possibility is normal reference value of vitamin D level might be low in South Asians compared to western countries. So, large scale research including all required parameters can solve these concerns and queries.